Chemical biology in the embryo: In situ imaging of sulfur biochemistry in normal and proteoglycan-deficient cartilage matrix - Hackett, Mark; George, G.; Pickering, I.; Eames, B. (American Chemical Society, 2016)
© 2016 American Chemical Society. Proteoglycans (PGs) are heavily glycosylated proteins that play major structural and biological roles in many tissues. Proteoglycans are abundant in cartilage extracellular matrix; their loss is a main feature of the joint disease osteoarthritis. Proteoglycan function is regulated by sulfation-sulfate ester formation with specific sugar residues. Visualization of sulfation within cartilage matrix would yield vital insights into its biological roles. We present synchrotron-based X-ray fluorescence imaging of developing zebrafish cartilage, providing the first in situ maps of sulfate ester distribution. Levels of both sulfur and sulfate esters decrease as cartilage develops through late phase differentiation (maturation or hypertrophy), suggesting a functional link between cartilage matrix sulfur content and chondrocyte differentiation. Genetic experiments confirm that sulfate ester levels were due to cartilage proteoglycans and support the hypothesis that sulfate ester levels regulate chondrocyte differentiation. Surprisingly, in the PG synthesis mutant, the total level of sulfur was not significantly reduced, suggesting sulfur is distributed in an alternative chemical form during lowered cartilage proteoglycan production. Fourier transform infrared imaging indicated increased levels of protein in the mutant fish, suggesting that this alternative sulfur form might be ascribed to an increased level of protein synthesis in the mutant fish, as part of a compensatory mechanism.